Nicotine and brain disorders - Mihailescu Stefan; Drucker-Colin Rene (Acta Pharmacologica Sinica, 2016)
During the last decade, brain nicotinic acetylcholine receptors were extensively characterized from electrophysiological and pharmacological points of view. These receptors play important roles in memory and cognition and participate in the pathogenesis of several brain disorders (Parkinson's and Alzheimer's diseases, Tourette's syndrome, schizophrenia, depression, attention deficit disorder). In the same diseases, clinical studies showed that nicotine had beneficial effects, both as therapeutic and prophylactic agent. This review presents recent data concerning the structure and properties of neuronal nicotinic receptors, their involvement in the pathogenesis of various brain disorders and the beneficial effects of nicotine as therapeutic agent.